Aplicação de computação estocástica à detecção de bordas em imagens digitais - Cavalcanti, Danilo Barreto (2019)
This work compares the grey image edge detection algorithm based on Sobel operators considering two implementations: conventional digital logic and Stochastic Computing. The latter refers to an unconventional way of organising and operating numbers, treating them as probabilities. There are advantages in noise robustness, integrated circuit area utilisation and power consumption, when compared to CMOS Digital Electronics, in certain applications. This work implemented and evaluated ﬁlters in software (Python) and hardware (Verilog/FPGA). It is shown that the order of magnitude of the diﬀerence between results in both versions is of two bits. It is shown that the stochastic approach is more robust to soft errors, while also having less discrepant error distributions between 1% and 5% of error bit rates. Finally, the number of logical gates and power required for each implementation is presented. This stablishes guidelines of cost-beneﬁt for energy eﬃcient Digital Electronics projects.